Pengaruh Struktur Modal terhadap Kinerja Perusahaan Pertanian yang terdaftar di Indeks Saham Syariah Indonesia - Suradi Suradi; Rusdiawan Rusdiawan (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study discusses the effect of capital structure on the performance of agricultural companies listed in the Indonesian Islamic stock index. This study aims to determine how the influence of short-term debt and long-term debt (Short-term Debt and Longterm Debt) on company performance (Return on Assets, Return on Equity, Net Profit Margin). The results showed that long-term debt and short-term debt affect the company's performance, but the percentage of short-term debt and long-term debt can not be used as a measure to assess the company's performance is good or bad, because there are companies that have short and long-term debt but it is able to produce a fairly good performance, and vice versa when the short-term debt and long-term debt of the company has a high percentage does not guarantee the company will perform well. One of the things that makes the percentage of the company's capital structure does not significantly affect company performance is market share. This happened because at that time the market segmentation did not support the sale of the company's products, so the company could suffer losses (Profit Loss).